👤

va rog sa ma ajutati nu le-am inteles.Calculati:x-y-z si (x+y-z)-(-x-y+z),unde x=-a+b-c;y=a-b-c;z=-a-b+c,iat a) a=5√5-3√2+2√3;b=√5-4√2-3√3;c=2√5-√3-5√2;                                                            b)a=6√5-5√2-4√3;b=3√5-4√2-6√3;c=-√5+2√3-6√2;                                                                c)a=4√5-7√2-3√3;b=-2√5+5√2-7√3;c=-3√5-3√2-5√3

Răspuns :

a) [tex]a=5 \sqrt{5} -3 \sqrt{2} +2 \sqrt{3} [/tex]
[tex]b= \sqrt{5} -4\sqrt{2} -3 \sqrt{3} [/tex]
[tex]c=2 \sqrt{5} - \sqrt{3} -5 \sqrt{2} [/tex]
[tex]x=-a+b-c[/tex]
[tex]x=-(5 \sqrt{5} -3 \sqrt{2} +2 \sqrt{3})+\sqrt{5} -4\sqrt{2} -3 \sqrt{3}-(2 \sqrt{5} - \sqrt{3} -5 \sqrt{2} )[/tex]
[tex]x=-5 \sqrt{5} +3 \sqrt{2} -2 \sqrt{3}+\sqrt{5} -4\sqrt{2} -3 \sqrt{3}-2 \sqrt{5}+\sqrt{3} +5 \sqrt{2} [/tex]
[tex]x=-6 \sqrt{5} +4 \sqrt{2} -4 \sqrt{3}[/tex]
[tex]y=a-b-c[/tex]
[tex]y=5 \sqrt{5} -3 \sqrt{2} +2 \sqrt{3}-(\sqrt{5} -4\sqrt{2} -3 \sqrt{3})-(2 \sqrt{5} - \sqrt{3} -5 \sqrt{2} )[/tex]
[tex]y=5 \sqrt{5} -3 \sqrt{2} +2 \sqrt{3}-\sqrt{5}+4\sqrt{2} +3 \sqrt{3}-2 \sqrt{5}+ \sqrt{3} +5 \sqrt{2} [/tex]
[tex]y=2\sqrt{5} -6 \sqrt{2} +6 \sqrt{3}[/tex]
[tex]z=-a-b+c[/tex]
[tex]z=-(5 \sqrt{5} -3 \sqrt{2} +2 \sqrt{3})-(\sqrt{5} -4\sqrt{2} -3 \sqrt{3})+(2 \sqrt{5} - \sqrt{3} -5 \sqrt{2} )[/tex]
[tex]z=-5 \sqrt{5} +3 \sqrt{2} -2 \sqrt{3}-\sqrt{5} +4\sqrt{2} +3 \sqrt{3}+2 \sqrt{5} - \sqrt{3} -5 \sqrt{2} [/tex]
[tex]z=-4 \sqrt{5} +2 \sqrt{2}[/tex] 

[tex]x-y-z=[/tex][tex]-6 \sqrt{5} +4 \sqrt{2} -4 \sqrt{3}-(2\sqrt{5} -6 \sqrt{2} +6 \sqrt{3})-(-4 \sqrt{5} +2 \sqrt{2})[/tex][tex]=-6 \sqrt{5} +4 \sqrt{2} -4 \sqrt{3}-2\sqrt{5} +6 \sqrt{2} -6 \sqrt{3}+4 \sqrt{5} -2 \sqrt{2}[/tex][tex]=-4 \sqrt{5} +8 \sqrt{2} -10 \sqrt{3}[/tex]
[tex](x+y-z)-(-x-y+z)=x+y-z+x+y-z=2x+2y-2z=[/tex][tex]2(x+y-z)[/tex]
[tex]2(x+y-z)[/tex][tex]=2*[-6 \sqrt{5} +4 \sqrt{2} -4 \sqrt{3}+2\sqrt{5} -6 \sqrt{2} +6 \sqrt{3}-(-4 \sqrt{5} +2 \sqrt{2})][/tex][tex]=2*(-6 \sqrt{5} +4 \sqrt{2} -4 \sqrt{3}+2\sqrt{5} -6 \sqrt{2} +6 \sqrt{3}+4 \sqrt{5} -2 \sqrt{2})[/tex][tex]=2*(-4 \sqrt{2} +2 \sqrt{3} )=-8 \sqrt{2} +4 \sqrt{3}[/tex]

b) [tex]a=6 \sqrt{5} +5 \sqrt{2} -4 \sqrt{3} [/tex]
[tex]b= 3\sqrt{5} -4\sqrt{2} -6 \sqrt{3} [/tex]
[tex]c=- \sqrt{5}+2\sqrt{3}-6 \sqrt{2} [/tex]
[tex]x=-a+b-c[/tex]
[tex]x=-(6 \sqrt{5} -5 \sqrt{2} -4 \sqrt{3})+ 3\sqrt{5} -4\sqrt{2} -6 \sqrt{3} -(- \sqrt{5}+2\sqrt{3}-6 \sqrt{2})[/tex][tex]=-6 \sqrt{5}+5 \sqrt{2} +4 \sqrt{3}+ 3\sqrt{5} -4\sqrt{2} -6 \sqrt{3} + \sqrt{5}-2\sqrt{3}+6 \sqrt{2}[/tex]
[tex]x=-2 \sqrt{5}-6 \sqrt{2} -4 \sqrt{3}[/tex]
[tex]y=a-b-c[/tex]
[tex]y=6 \sqrt{5} -5 \sqrt{2} -4 \sqrt{3}-( 3\sqrt{5} -4\sqrt{2} -6 \sqrt{3}) -(- \sqrt{5}+2\sqrt{3}-6 \sqrt{2})[/tex][tex]=6 \sqrt{5}-5 \sqrt{2} -44 \sqrt{3}- 3\sqrt{5} +4\sqrt{2} +6 \sqrt{3} + \sqrt{5}-2\sqrt{3}+6 \sqrt{2}[/tex]
[tex]y=4 \sqrt{5}+5 \sqrt{2}[/tex]
[tex]z=-a-b+c[/tex]
[tex]z=-(6 \sqrt{5} -5 \sqrt{2} -4 \sqrt{3})-( 3\sqrt{5} -4\sqrt{2} -6 \sqrt{3} )- \sqrt{5}+2\sqrt{3}-6 \sqrt{2}[/tex][tex]=-6 \sqrt{5}+5 \sqrt{2} +4 \sqrt{3}- 3\sqrt{5} +4\sqrt{2}+6 \sqrt{3} - \sqrt{5}+2\sqrt{3}-6 \sqrt{2}[/tex]
[tex]z=-10 \sqrt{5}+4\sqrt{2}+12\sqrt{3}[/tex]
[tex]x-y-z=[/tex][tex]-2 \sqrt{5} -6 \sqrt{2} -4 \sqrt{3}-4\sqrt{5}-5\sqrt{2} +10\sqrt{5}-4 \sqrt{2}-12 \sqrt{3} = [/tex][tex]4 \sqrt{5} -15 \sqrt{2} -16\sqrt{3}[/tex]
[tex](x+y-z)-(-x-y+z)=x+y-z+x+y-z=2x+2y-2z=[/tex][tex]2(x+y-z)[/tex]
[tex]2(x+y-z)[/tex]=[tex]2*(-2 \sqrt{5} -6 \sqrt{2} -4 \sqrt{3}+4\sqrt{5}+5\sqrt{2} +10\sqrt{5}-4 \sqrt{2}-12 \sqrt{3})[/tex]=[tex]=2*(12 \sqrt{5} -5 \sqrt{2} -16 \sqrt{3})=24 \sqrt{5} -10 \sqrt{2} -32 \sqrt{3}[/tex]

c)[tex]a=4 \sqrt{5} -7 \sqrt{2} -3 \sqrt{3} [/tex]
[tex]b=-2 \sqrt{5} +5\sqrt{2} -7 \sqrt{3} [/tex]
[tex]c=-3 \sqrt{5} -3 \sqrt{2} -5 \sqrt{3} [/tex]
[tex]x=-a+b-c[/tex][tex]=-(4 \sqrt{5} -7 \sqrt{2} -3 \sqrt{3})-2 \sqrt{5} +5\sqrt{2} -7 \sqrt{3}-(-3 \sqrt{5} -3 \sqrt{2} -5 \sqrt{3})[/tex][tex]=-4 \sqrt{5} +7 \sqrt{2} +3 \sqrt{3}-2 \sqrt{5} +5\sqrt{2} -7 \sqrt{3}+3 \sqrt{5} +3 \sqrt{2} +5 \sqrt{3}[/tex][tex]=-3 \sqrt{5} +15\sqrt{2} + \sqrt{3}[/tex]
[tex]y=a-b-c[/tex][tex]=4 \sqrt{5} -7 \sqrt{2} -3 \sqrt{3} -(-2 \sqrt{5} +5\sqrt{2} -7 \sqrt{3})-(-3 \sqrt{5} -3 \sqrt{2} -5 \sqrt{3})[/tex][tex]=4 \sqrt{5} -7 \sqrt{2} -3 \sqrt{3} +2 \sqrt{5} -5\sqrt{2} +7 \sqrt{3}+3 \sqrt{5} +3 \sqrt{2} +5 \sqrt{3}[/tex][tex]=9 \sqrt{5} -9 \sqrt{2} -9 \sqrt{3}[/tex]
[tex]z=-a-b+c[/tex][tex]=4 \sqrt{5} -7 \sqrt{2} -3 \sqrt{3}-(-2 \sqrt{5} +5\sqrt{2} -7 \sqrt{3})-3 \sqrt{5} -3 \sqrt{2} -5 \sqrt{3}[/tex][tex]=4 \sqrt{5} -7 \sqrt{2} -3 \sqrt{3}+2 \sqrt{5}-5\sqrt{2} +7 \sqrt{3}-3 \sqrt{5} -3 \sqrt{2} -5 \sqrt{3}[/tex][tex]=3\sqrt{5} -15 \sqrt{2} -\sqrt{3}[/tex]

[tex]x-y-z=[/tex][tex]-3 \sqrt{5} +15\sqrt{2} + \sqrt{3}-(9 \sqrt{5} -9 \sqrt{2} -9 \sqrt{3})-(3\sqrt{5} -15 \sqrt{2} -\sqrt{3})[/tex][tex]=-3 \sqrt{5} +15\sqrt{2} + \sqrt{3}-9 \sqrt{5} +9 \sqrt{2} +9 \sqrt{3})-3\sqrt{5} +15 \sqrt{2} +\sqrt{3}[/tex] [tex]=-15 \sqrt{5} +39\sqrt{2} +11 \sqrt{3}[/tex]
[tex](x+y-z)-(-x-y+z)=x+y-z+x+y-z=2x+2y-2z=[/tex][tex]2(x+y-z)[/tex]
[tex]2(x+y-z)[/tex][tex]=2[-3 \sqrt{5} +15\sqrt{2} + \sqrt{3}+9 \sqrt{5} -9 \sqrt{2} -9 \sqrt{3}-(3\sqrt{5} -15 \sqrt{2} -\sqrt{3})][/tex][tex]=2(-3 \sqrt{5} +15\sqrt{2} + \sqrt{3}+9 \sqrt{5} -9 \sqrt{2} -9 \sqrt{3}-3\sqrt{5} +15 \sqrt{2} +\sqrt{3})[/tex][tex]=2(-3 \sqrt{5} +21\sqrt{2} -7 \sqrt{3})=-6\sqrt{5}+42\sqrt{2}-14 \sqrt{3}[/tex]